Challenges related to the use of liquid metal and molten salt coolants in advanced reactors : report of the Collaborative Project COOL of the International Project on Innovative Nuclear Reactors and Fuel Cycles (INPRO). (IAEA-TECDOC ;, 2013)
"This publication documents the results of experimental investigations and computational fluid dynamics studies on thermal hydraulics, specifically models and correlations on pressure drop and heat transfer involving to liquid metal and molten salt coolants under different operating conditions, including the feedback on neutronics effects. It presents new or verifies existing data on thermo-physical properties of liquid metal and molten salt coolants, and describes tools for on-line monitoring and control of coolant chemistry. Methods to improve the corrosion resistance between heavy liquid metal coolant and components, structure material and instrumentation are also examined."--Publisher's description.